Simbolisme Makanan dalam Cerita Anak Bancakan: Kajian Gastrosemiotik untuk Pendidikan Humanis Masa Depan - Liana Rochmatul Wachidah; Heny Subandiyah; Titik Indarti (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The Bancakan folk tale represents a simple yet meaningful tradition of celebration through food offerings. This study uses a gastro-semiotic-ethnographic approach to reveal the function of food in the story as a cultural symbol and inspiration for humanistic education. The method used is qualitative descriptive-text analysis with the data source being the folk tale titled Bancakan by Sudadi. Data was collected through reading, note-taking, and mapping signs and values. It was analyzed using a framework of gastronomy, semiotics, and ethnography, supported by Causal Layered Analysis (CLA). The research findings reveal that food in the story, such as nasi gunungan, urap, boiled eggs, salted fish, and nasi gandulan (rice sent to an absent child), represents prayers, hopes, togetherness, and care. This aligns with Javanese cultural practices that emphasize togetherness and acceptance (nrima). Through CLA, the symbolism of these foods is projected into future education through a love-based curriculum rooted in compassion, empathy, and solidarity. The novelty of this research lies in the integration of gastrosemiotic ethnography and CLA, positioning culinary folk tales not merely as cultural heritage but as a source of inspiration for humanistic education grounded in local wisdom.